Maintenance management of public building managed by Subang Jaya Municipal Council (MPSJ) / Noor Aqmar Mohd Rusly - Mohd Rusly, Noor Aqmar (2009)
Maintenance management means the aspect of management that will lead the work on maintaining a building. MPSJ is the local authority that has many assets to manage including its public building which needs a proper maintenance management to prevent from deterioration. Two types of maintenance system implemented by MPSJ are In-Housed and Out Sourced. The aim of this study is to identify this system in the public building managed by MPSJ. To achieve the aim, three objectives have been set up to study on process of managing maintenance works for public building managed by MPSJ, to determine the satisfaction of the public on the maintenance management of public building managed by MPSJ and to identify problems in maintenance management managed by MPSJ. In order to achieve the objectives, the interview and literature review was done and data has been collected using questionnaires. The out put of research from data analysis is achieved by Microsoft Excel 2003. Finding shows that there need an improvement in maintenance management managed by MPSJ in terms of performance, planning, timely response and quality of maintenance works need to be improve to achieved high satisfaction level on maintenance management. To improve the current maintenance management for public building is by providing control and monitor system and develop good and practical system to control a performance, planning and quality of maintenance works.